Public Trust Recovery: the Role of Digital Government Public Relations and AI-Assisted Crisis Communication - Rosmala; Ali Salman (INJECT (Interdisciplinary Journal of Communication), 2026)
The recent sting operation involving the Governor of Riau has triggered a significant public trust crisis toward the local government. This situation underscored the urgent need for a more adaptive, transparent, and technology-driven governance system. This study aimed to examine the influence of Digital Government Public Relations and AI-Assisted Crisis Communication on Public Trust Recovery in Riau Province. A quantitative study design was employed, utilizing an online survey distributed via Google Forms to 150 residents of Pekanbaru. The collected data were analyzed by using multiple linear regression. The findings indicated that Digital Government Public Relations exerted a positive and significant effect on public trust recovery by enhancing the transparency and accessibility of government information. Furthermore, AI-Assisted Crisis Communication also demonstrated a significant impact through faster crisis response, message consistency, and analytics-based detection of misinformation. Collectively, both variables contributed to rebuilding public trust in the aftermath of political crises. The study highlighted the importance of digital communication governance and the integration of artificial intelligence in modern governmental communication strategies to strengthen legitimacy, credibility, and public confidence.